(untitled) (Global Journal of Science Frontier Research, 2018)
The CDMFF theory presented in the book "The Great Cosmic Sea" will explain how the evolution of our planet and its biosphere is actively evolving with our cosmos through a complex network of powerful morphogenetic fields at all scales. This theory explains many of the findings revealed by scientific evidence of the nature of the fabric of our cosmic sea in which we coexist with each other and other worlds, both terrestrial and extraterrestrial. Most of the concepts of this theory are now under copyright protection in a book soon to be released. However, what I am revealing in this invited paper is a new insight not currently a part of that publication. The foundations of this theory pave the way to understand a possible source of virtual particles thought to be present at the Planck scale. It is possible that virtual particles are being produced by the Hawking radiation, as well as, released as morphogenetic fields are traversing the baryonic matter/dark matter junction (BM/CDMFF/I) and striped of the atomic structure within by Planck virtual black holes(PVBH’s).